Vulnerabilidade intrínseca e risco de contaminação do aquífero livre da bacia hidrográfica do Rio Gramame-PB - Linhares, Franklin Mendonça (2012)
The vulnerability mapping and risk analysis of groundwater contamination are essential for guiding management plans of watersheds. Currently, new criteria for eligibility of groundwater are required by CONAMA Resolution No. 396/2008 and justifies this study. The chosen basin for mapping of vulnerability of a free aquifer was the Gramame river basin in Paraíba State. To build the vulnerability map the DRASTIC method was chosen, acronym of factors to be analyzed: Depth to the water table, net Recharge, Aquifer media, Soil media, Topography, Impact of the unsaturate zone, Hydraulic Condutivity. For the pollution risk mapping the modified DRASTIC was used, where the characteristics of land use and land cover are also considered. Each DRASTIC factor is built dynamically as a layer of a Geographic Information System (GIS). Environment features of the system are specialized and, in the final step, are integrated in order to generate vulnerability map. The preliminary risk analysis is made by overlapping the vulnerability map to the land cover and land use maps. Data from static levels of 27 shallow wells were collected monthly during a hydrological year (2010/2011), which allowed to divide them into two periods: wet and dry. With this determination it was possible to compare the vulnerability maps for these two distinct periods. It was found in this study that, in the rainy season, the vulnerability is greater than in the dry season. The result of the intrinsic vulnerability map in the rainy season showed that the central and southwest regions, where the city of Pedras de Fogo is located, presents high vulnerability. The risk of contamination map identified these same regions as very high risk due to human action. These data can be used to define and direct resources to areas where protection is needed, as well as subsidize the municipal and state management in making decisions regarding land use, actions development and measures to ensure the environmental quality of the groundwater of Gramame river basin.